Teamworking in endoscopy: a human factors toolkit for the COVID-19 era - Ravindran, Srivathsan; Matharoo, Manmeet; Coleman, Mark; Marshall, Sarah; Healey, Chris; Penman, Ian; Thomas-Gibson, Siwan (Endoscopy, 2020)
Background Endoscopy services have had to rapidly adapt their working practices in response to COVID-19. As recovery of endoscopy services proceeds, our workforce faces numerous challenges that can impair effective teamworking. We designed and developed a novel toolkit to support teamworking in endoscopy during the pandemic.Methods A human factors model was developed to understand the impact of COVID-19 on endoscopy teams. From this, we identified a set of key teamworking goals, which informed the development of a toolkit to support several team processes. The toolkit was refined following expert input and refinement over a 6-week period. Results The toolkit consists of four cognitive aids that can be used to support team huddles, briefings, and debriefs, alongside techniques to optimize endoscopic nontechnical skills across the patient-procedure pathway. We describe the processes that local endoscopy units can employ to implement this toolkit. Conclusion A toolkit of cognitive aids, based on human factors principles, may be useful in supporting teams, helping them adapt to working safely in the era of COVID-19.